Implementasi User Centered Design Pada Rancangan Pengembangan UX Aplikasi Pendataan Kegiatan Marketing - Wachiddin M Huda; Pristi Sukmasetya; Emilya Ully Artha (JURIKOM (Jurnal Riset Komputer), 2022)
The Roadshow application is an application used by the Marketing Unit of the Universitas Muhammadiyah Magelang to help collect data on their activities. In the process of using it, users often experience problems when operating the Roadshow application. This can also be seen from the preliminary research results which show that the results of the User Experience assessment are still low. To overcome this, development is needed to improve the user experience of the roadshow application so that it can improve the performance of the Marketing Unit. User-Centered Design (UCD) was chosen as the design development method. The UCD approach was chosen because it emphasizes specific user needs without changing their behavior in using the system or application. User testing is done by using the prototype made. The results of Usability Concept testing generate positive feedback from users. The evaluation was carried out on the same user using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). From the results of SUS, a score of 88 out of 100 was obtained and UEQ was ranked Good and above with an average score of 1.8. From the process of testing and evaluating the user experience design of the Roadshow application, it can be said to be good and can be a recommendation for the development of the Roadshow application in the future.